INDEPENDENT CURRICULUM: PANCASILA STUDENT PROFILE THROUGH PPKn LEARNING - Supriadi; Dhayinta, Shellya Tanaya; Rafid, Rahmad; Anshori, Ibnu (Four Son Scholarship, 2024)
This research aims to examine the implementation of the Merdeka Curriculum in forming Pancasila student profiles through the integration of Pancasila and Citizenship Education subjects at Abu Ghonaim Bumiaji Batu Islamic Middle School. This research uses a qualitative approach with descriptive methodology. Data collection tools consist of observation, interviews and documentation. The research findings show that the aim is to increase the components of the Pancasila student profile through the formulation of Civics learning modules. The teacher's role in implementing Citizenship Education through strengthening the dimensions of the Pancasila student profile includes: acting as a role model, inspirer, learning planner, elaboration of Pancasila values, model project facilitator, motivator, and assessor. The implementation of the Pancasila student profile through PPKn learning is facilitated by several key factors, including the dedication of teaching staff, the selection of students who are committed to the program, the provision of adequate learning facilities, the development of effective learning methods, and the active involvement of the school committee and the wider community.